PENGARUH SANITASI MAKANAN TERHADAP KEJADIAN DIARE PADA BALITA DI DESA KEDONDONG KECAMATAN SOKARAJA - Etika Dewi Cahyaningrum (Viva Medika, 2012)
Diarrhea is the defecation with a liquid faeces or semi-liquid and the content of stools more than 200 ml/24 hours. In developing countries is estimated at more than 5 millionchildren die every year from diarrhea. Diarrhea cases in Central Java was ranked secondwith the data of outpatient visits in health centers and the ranked is 195.907, or 10.46% ofthe 1,873,114 patients and inpatient in hospital for 12 719 or 36.27%, it menas diarrheaincluding one incident Extraordinary (KLB) in Central Java. The results of a preliminarystudy on the population with 5 people who were live at Kedondong village, three mothers ofchildren who had diarrhea of which mention had been treated in hospital. Two people amongthose also explained that diarrhea disease in children is caused due to the provision of cleanwater, food hygiene toddlers, and the factor of the perception that it is infectious diarrheadirectly. Based on this phenomenom, the authors interested in studying the effects of foodsanitation on the incidence of diarrhea in the village of the District Kedondong Sokaraja. The design of the research is analytic survey with cross sectional approach. Bivariatestatistical tests in this study is done by using Chi Square test is used to estimate the frequencyof the investigated or analyzed the results of observation to determine whether there is arelationship or a significant difference. Keywords: sanitation, diarrhea, toddlers